Analysis Of Financial Performance Affecting Corporate Value - et. al., R. Ait Novatiani, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Firm value is the investor's perception of the company's success rate which is often associated with stock prices, where high stock prices make the company value high. Factors that can affect firm value are financial performance where the better the financial performance of a company, the better the company value, which consequently the level of investor confidence in the company will be better.The research data sample was obtained by purposive sampling method, amounting to 26 property companies listed on the Indonesia Stock Exchange. The results showed that liquidity had an effect on firm value and profitability had an effect on firm value.